Anomalous Lateral Rectus Muscle Band in a Case of Duane Retraction Syndrome. (2nd October 2017) - Ganesh, Suma; Tibrewal, Shailja; Yadav, Abhijeet; Sethi, Sumita
ABSTRACT: Anomalous orbital structures are suspected in restrictive strabismus with features of severe globe retractions, overshoots, or synergistic movements. We report a case of suspected Duane syndrome that was found to have an anomalous band beneath the lateral rectus muscle. Such abnormal structures are rare, but it is important to identify and manage them to optimize outcomes.